“If you don't know my story, please don't judge my walk”: a critical autoethnographic journey of a Black female counselor transitioning to DEIB leadership - Cheeks, Ralita (Kansas State University, 2024)
This critical autoethnographic dissertation delves into the personal journey of a Black female counselor and mother, whose path meanders through the complex terrain of education, leading her to a profound transition into the realm of Diversity, Equity, Inclusion, and Belonging (DEIB) leadership. Drawing from memories, emotions, and ongoing encounters, this critical autoethnography uses braiding as a framework for bringing together stories of identity development, self-reflection, cultural context, social dynamics, while working at the intersection of various counseling and leadership frameworks alongside Black feminism, spirituality, and motherhood. Stories of belonging, faith, family, and community emerge in harmonious and dissonant ways through the autoethnographic process. Yet, these stories also serve as crucial anchors for starting a courageous conversation during a personal and professional transition to DEIB leadership roles. Furthermore, these stories shape the author's sense of self and social presence, along with themes of vulnerability and empowerment while working through systems which intertwine, showcasing the transformative potential of embracing one's unique voice.
Keywords: School counseling; Diversity; Equity; Inclusion; Belonging; Black female